Efek Moderasi Tingkat Konvergensi IFRS atas Pengaruh Accrual Reversal terhadap Persistensi Laba dan Respon Pasar - Khomsatun, Siti (Jurnal Riset Akuntansi dan Keuangan, 2018)
The study aims to analyze moderating effect of IFRS convergence on the relationship accrual reversal with earning persistence and market response. The study used 1158 unbalances panel data from non-financial company listed in Indonesian stock exchange for period 2007-2012. Using generalized least squared, the results show that the accrual estimation error is the least persistent component of earning. In detail, accrual relating temporary fluctuation in working capital has more persistent than cash flow, but accrual relating firm growth is not found significantly effecting on earning persistent. The main result shows that IFRS convergence influences the relationship between accrual reversal and earning persistence, but it is not found in the relationship between accrual reversal and stock return. This result indicates that IFRS convergence can support manager has a better judgment precision, but investors still overprice cash flow and underprice accrual